Customizable assembly of free-standing integrated electronics for wearables by phase separation. Issue 96 (14th November 2022) - Ma, Hongting; Chen, Chuanrui; Cheng, Peihao; Yang, Kaizhou; Geng, Xiaodong; Ma, Junlin; Lv, Fengjuan; Jiang, Yue; Liu, Quanli; Su, Yan; Li, Jian; Zhu, Nan
Abstract : A free-standing electronic device, including an ethanol fuel cell, a supercapacitor and a motion sensor, was fabricated by non-solvent induced phase separation. Abstract : The non-solvent induced phase separation method is utilized to produce a free-standing electrode with good conductivity retention during 1000 bending/stretching cycles. The as-prepared electrode has been fabricated for an integrated device consisting of an ethanol fuel cell, a supercapacitor and a motion sensor. This method for fabricating free-standing electronics reveals a cost-effective approach towards wearable devices.